A. Given the equation 4x + 7 = 3(2x − 5), solve for the variable. Explain each step and justify your process.
2 answers:
<span>A. Given the equation 4x + 7 = 3(2x − 5), solve for the variable. </span>4x + 7 = 3(2x − 5) <span>4x + 7 = 6x - 15 (distributive property of multiplication) 4x - 6x = -15 - 7 (transitive property) -2x = -22 x = 11 B. Sam solved a similar equation below. Is Sam's solution correct? Explain why or why not. 5x − 1 = 2(x + 4) 5x − 1 = 2x + 8 7x − 1 = 8 7x = 7 x = 1 Sam's solution is incorrect, this is the correct solution </span>5x − 1 = 2(x + 4) 5x − 1 = 2x + 8 5x − 2x = 8 + 1 3x = 9 x = 3
You might be interested in
P<6, but depending on the axis the grip will be different. if it is on an x axis it will be the first graph and if it is y then it will be the second graph attached.
A vertical line that passes through (-5,0)
Answer: 2z + 6
Step-by-step explanation: Distribute the 2 to z and 3.
Answer:
No solution
Step-by-step explanation:
I got it right on delta math, just dont write anything and turn that in and it should be correct.
-6 1/3 because it looks less than -6.375 which would mean that it is in fact bigger on the number scale.